Potensi Biji Nangka (Artocarpus heterophyllus) Sebagai Media Alternatif Pertumbuhan Jamur Aspergillus sp - Zulfian Armah; Rezi Anggreani; Herdiana Herdiana; Muhammad Nasir; Rahman Rahman (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Jackfruit seeds are one of the organic wastes that have not been optimally utilized, even though they have high nutritional content, especially carbohydrates. This composition makes jackfruit seeds a potential alternative medium for supporting fungal growth. The alternative medium made from jackfruit seeds is produced by processing the seed extract into a natural growing medium. The objective of this study was to evaluate the growth of Aspergillus sp fungi on an alternative medium made from jackfruit seed extract. The study was conducted using observational and experimental methods in a laboratory, comparing the growth of Aspergillus sp colonies at three media concentrations: 20%, 40%, and 60%. The research was carried out at the Microbiology Laboratory, Department of Medical Laboratory Technology, Poltekkes Kemenkes Makassar in April 2024. Jackfruit seed extract was used as the main medium for fungal growth. The results showed that the average colony diameter of Aspergillus flavus over five consecutive days on jackfruit seed extract medium at a concentration of 20% was 33.7 mm, 40% was 33.9 mm, and 60% was 41.7 mm. A concentration of 60% was found to be the most effective medium for fungal growth. Further research is recommended to explore other concentrations, use jackfruit seed decoction, and eliminate the addition of dextrose in the medium composition. Keywords: Aspergillus sp, jackfruit seeds, alternative medium